If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7y + -7 = 8 + 6y Reorder the terms: -7 + 7y = 8 + 6y Solving -7 + 7y = 8 + 6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6y' to each side of the equation. -7 + 7y + -6y = 8 + 6y + -6y Combine like terms: 7y + -6y = 1y -7 + 1y = 8 + 6y + -6y Combine like terms: 6y + -6y = 0 -7 + 1y = 8 + 0 -7 + 1y = 8 Add '7' to each side of the equation. -7 + 7 + 1y = 8 + 7 Combine like terms: -7 + 7 = 0 0 + 1y = 8 + 7 1y = 8 + 7 Combine like terms: 8 + 7 = 15 1y = 15 Divide each side by '1'. y = 15 Simplifying y = 15
| f(x)=-26x^2-10 | | 18x^8y^8/10x^3 | | 156x-16x^2=0 | | .4A+.25(1-A)=.32 | | .4A+.25(1-A)=.32(220000) | | 0.7=904 | | 50+3x=10(x-2) | | 4y^4/14yx^8 | | 3x+17+5x+21=180-14y | | -5(2x-6)=4(x+47) | | X=18/4; | | 12x+2=180-14y | | 2cos^2x/2-3cosx=0 | | 3(w-7)=-66 | | 1s+5x= | | 0.034=0.21x+0.046 | | 13(y-3)=-52 | | 0.034=636.63x+0.068 | | 30+0.08x=19+0.12x | | 2(x^4-6x^2)^2/3=18 | | -0.6x+6.39=-0.8x+0.39 | | 13(c-3)=-52 | | 1.68x+15=2.38x-20 | | -(3-x)-4x+9=-2(2x-5)+8 | | 3x+3=7-(4x-9) | | 4.75-7= | | X^4-6x^2=1458 | | m=4.75 | | 4(x-2)-2=6 | | 2(3y+2)=0.5(12y+8) | | 6(y+9)=7y+52 | | 16n=22+5n |